JENIS SENYAWA ORGANIK SUPLEMEN PADA MEDIUM KNUDSON C UNTUK PERTUMBUHAN PROTOCORM LIKE BODIES DENDROBIUM BERTACONG BLUE X DENDROBIUM UNDULATUM - Syammiah Syammiah (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2006)
The Organic Compound Supplement in Knudson C Medium on The Growth of Protocorm Like Bodies of Dendrobium Bertacong Blue X Dendrobium Undulatum Syammiah Fakultas Pertanian Universitas Syiah Kuala Banda Aceh ABSTRACT The aim of this research was to find out the best modification on Knudson C medium for the growth of protocorm like bodies of Dendrobium bertachong blue X Dendrobium undulatum in vitro. Research has been done for three months from April to July 2005. Completely Randomized Design with 6 treatments and 4 replications was applied. The treatments were Knudson C medium added with: 15% of coconut liquid endosperm, 7.5% of banana juice, 0.2% of yeast extract, 15% of potato juice, 5% of aloe juice, and 5% of tomato juice. The results showed that 5% of tomato juice was the fastest for shoot forming and 5% of aloe juice was the best medium supplement for the colour of protocorm like bodies.